Trio-based whole exome sequencing in patients with ectopic posterior pituitary - Lyra, Arthur; Rodart, Itatiana Ferreira; Barros, Lara; Silva, Tatiane Sousa e; da Rocha, Antônio José; Kochi, Cristiane; Longui, Carlos Alberto (Frontiers in Pediatrics, 2024)
Introduction: Ectopic posterior pituitary (EPP) is a rare congenital abnormality, sometimes associated with other midline defects, such as pituitary stalk interruption syndrome (PSIS), in which thin or absent pituitary stalk and anterior pituitary hypoplasia are combined to EPP. Most cases are sporadic, with few reports of familial cases, and many congenital hypopituitarism (CH) cases remain unsolved. Objective: To search for candidate genes associated with this condition, we performed trio-based whole-exome sequencing (WES) on patients with EPP, including two familial cases. Methods: This study included subjects with EPP and PSIS diagnosed by a simple MRI protocol (FAST1.2). We performed two distinct analyses in the trio-based WES. We looked for previously described genes associated with pituitary development. Next, we investigated the whole exome for variants inherited in a pattern consistent with a monogenic etiology. Results: Ten families were evaluated; eight were composed of a child with EPP and healthy parents, one has two affected siblings, and one family has a son and mother with EPP. When analyzing the previously described candidate variants associated with pituitary development, we found variants in GLI2 and FGFR1 in three families. We also found six other variants of interest in three patients: KMT2A, MAP1AGALR3, RTN4R, SEMA3A, NIPBL, and DSCAML1. Conclusion: The analysis allowed us to find previously reported and not reported GLI2 variants, all inherited from healthy parents, which reinforces the incomplete penetrance pattern of GLI2 variants in the development of EPP and draws attention to possible future functional studies of those variants that have a recurrent expression in CH. We also found novel FGFR1 and SEMA3A variants that suggest an oligogenic mechanism in PSIS and EPP, as seen in patients with hypogonadotropic hypogonadism.We report the first case of a patient with Wiedemann-Steiner syndrome and PSIS, suggesting that the KMT2A gene may be related to pituitary development. Furthermore, the trios' analysis allowed 2 us to find five other variants of interest. Future investigations may clarify the roles of these variants in the etiology of EPP and PSIS.